(untitled) (Baghdad Science Journal, 2024)
Nano Platinum was used as a new photocatalyst, which was loaded onto graphene for an effective photocatalyst under UV light used in dye photodegradation applications of dye as a common pollutant for water. Thus, platinum loaded on graphene (Pt/ GNS) catalyst was prepared by the sol immobilization method. The morphology of the synthetic photocatalyst has been characterized and investigated using a High-resolution Transmission electron microscope (HRTEM) and Energy Dispersive X-ray spectroscopy (EDX) attached to FESEM. By measuring the adsorption/adsorption N2 using a Micrometrics surface analyzer, the Brunauer−Emmett−Teller (BET) surface areas of the photocatalysts were determined. The photocatalyst’s crystalline structure was also examined using the Powder X-ray Diffraction (XRD) technique. Previously prepared catalysts have been examined under UV light as effective photocatalysts to degrade the bromophenol blue dye. The first step was the radiation of dye with no catalyst and the results show that there is demand for photocatalysts to make a reaction. The optimal values of Nano Platinum determined by the catalyst that was prepared by sol immobilization method. The effect of pH on the degradation reaction was measured, where it was specified that the basic media was the suitable media for the reaction.